Musical monsters of Turkey Hollow - Langridge, Roger (Archaia, 2014)
Turkey Hollow is a picturesque town where hundreds of years ago, unbeknownst to the citizens, a meteorite landed nearby a small brook on the outskirts of town. One Thanksgiving, while young Timmy Henderson practices his guitar, hes accompanied by strange, unearthly, musical sounds. That meteorite wasnt a rock at all but an egg holding seven furry, goofy monsters, each with a unique musical sound. After the initial shock, Timmy befriends the lovable creatures following him all around Turkey Hollow. Not everyone takes a liking to the visitors though and its up to Timmy to protect his new friends and save Thanksgiving!